The Effect of Teacher Performance and Learning Media on Learning Outcomes of Elementary School Students - Angraini, Septa; Fitria, Happy; Setiawan, Andi Arif (Yayasan Sembilan Pemuda Indonesia, 2021)
This study aimed at determining the effect of teacher performance and learning media partially or simultaneously on student learning outcomes in SD District of East Baturaja. This research was a qualitative with sampling using random sampling technique. The study population amounted to 273 with a study sample of 108 people. The variables studied were teacher performance (X1), learning media (X2) and learning outcomes (Y). The data collection method used a questionnaire on the scale of teacher performance, the scale of learning media and student learning outcomes. The validity test was carried out with the help of a computer program SPSS 22 for windows. Reliability test using Cronbach's alpha technique, obtained p = 0, 986 for teacher performance variables and p = 0.987 for learning media variables. The data analysis technique is descriptive and inferential statistics with SPSS 22 for windows program. The results showed that there was an influence between teacher performance and learning media on student learning outcomes.